Draft Annual Plan 1989-90 Part I-Outline Union Territory of Delhi - Planning Commission (Planning Commission, 1988)
The population of the Union Territory of Delhi has been increasing at a phenomenal rate, particularly since 1941. The population of Delhi which was 17.44 lakhs in 1951 is now more than 80 lakhs. The rate of population growth in Delhi is more than double the rate of growth for the country as a whole. This is inspire of the fact that the birth rate in Delhi is 27 per thousand against the national average of 33 per thousand. Migration from other parts of the country was the major contributory factor of the rapid growth of population which accounts for more than 50 % of the total increase. The population of Delhi 5 s currently increasing fast at a rate- of over 3 Lakhs persons per year and it is estimated that the population of Delhi would go to 140 Million by 2001 A.D.
Union Territory of Delhi
Planning Department Delhi Administration
Keywords: Medium Irrigation; Flood Control; Energy; Industry & Minerals; Science; Technology & Environment; General Economy Services; Survey & Statistics; Civil Supplies; Weights & Measures; Technical Education; Sports Youth Services; Public Health; Water Supply & Sanitation; Jail Building; Stationery & Printing; Staff Training